The effect of the Posner model using a variety of kinetic exercises in learning the skill of peaceful basketball scoring (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare educational units with the Posner model using various kinetic exercises in learning and implementing the skills of soccer scoring and dribbling. The researcher used the experimental method for its suitability with the nature of the problem and the objectives of the research, as the experimental method is one of the best scientific research methods to solve problems. 20 students from class A were chosen to represent the control group and 20 students from class B to represent the experimental group.One of the most important conclusions of the research is that the use of the Posner model encouraged students to contribute to creativity and self-correct their information in proportion to their experiences, skills and personal talents that Posner model has a positive effect on the units Learning using a variety of motor exercises and learning the skills of soccer scoring and dribbling, and through the results of all skill tests, the students’ learning levels improved better and their cognitive abilities increased for the skills under study. Traditional ways that bring boredom